The Texas Health Resources Clinical Scholars Program: Learning healthcare system workforce development through embedded translational research - Andrew L. Masica; Ferdinand Velasco; Tanna L. Nelson; Richard J. Medford; Amy E. Hughes; Ambarish Pandey; Eric D. Peterson; Christoph U. Lehmann (Wiley, 2022)
Abstract Introduction Texas Health Resources (THR), a large, nonprofit health care system based in the Dallas‐Fort Worth area, has collaborated with the University of Texas Southwestern Medical Center (UTSW) to develop and operate a unique, integrated approach for Learning Health System (LHS) workforce development. This training model centers on academic health system faculty members conducting later‐stage translational research within a partnering regional care delivery organization. Methods The THR Clinical Scholars Program engages early career UTSW faculty members to conduct studies that are likely to have an impact on care delivery at the health system level. Interested candidates submit formal applications to the program. A joint committee comprised of senior research faculty from UTSW and THR clinical leadership reviews proposals with a focus on the shared LHS needs of both institutions-developing high quality research output that can be applied to enhance care delivery. A key prioritization criterion for funding is the degree to which the research addresses a question relevant to THR as a high‐volume network with multiple channels for consumers to access care. The program emphasis is on supporting embedded research initiatives using health system data to generate knowledge that will improve the quality and efficiency of care for the patient populations served by the participant organizations. Results We discuss specific strategic and tactical components of the THR Clinical Scholars Program including an overview of the academic affiliation agreement between the collaborating organizations, criteria for successful program applications, data sharing, and funding. We also share project summaries from selected clinical scholars as examples of the LHS research done in the program to date. Conclusion This experience report provides an implementation framework for other academic health systems interested in adopting similar LHS workforce training models with community partners.